2012
DOI: 10.1002/da.21996
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aripiprazole Augmentation in Treatment-Resistant Obsessive-Compulsive Disorder (A Double Blind Clinical Trial)

Abstract: Results of the present study indicate that aripiprazole could be an effective augmentation medicine in treatment resistant OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
3
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 22 publications
2
52
3
3
Order By: Relevance
“…Aripiprazolle ilgili sonuçlar net olmamakla beraber dirençli OKB hastalarında yapılan çift kör bir çalışmada aripiprazolün faydalı olduğu gösterilmiştir. 7 Onikofajinin eşlik ettiği yaygın anksiyete bozukluğu hastasında essitaloprama aripiprazol eklenmesi ile onikofaji semptomlarının düzelmesi ve bu faydanın takiplerde de devam etmesi önerimizi desteklemektedir. Sonuç olarak, onikofajisi olan yaygın anksiyete bozukluğu hastalarında tedaviye aripiprazol eklenmesi faydalı olabilir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aripiprazolle ilgili sonuçlar net olmamakla beraber dirençli OKB hastalarında yapılan çift kör bir çalışmada aripiprazolün faydalı olduğu gösterilmiştir. 7 Onikofajinin eşlik ettiği yaygın anksiyete bozukluğu hastasında essitaloprama aripiprazol eklenmesi ile onikofaji semptomlarının düzelmesi ve bu faydanın takiplerde de devam etmesi önerimizi desteklemektedir. Sonuç olarak, onikofajisi olan yaygın anksiyete bozukluğu hastalarında tedaviye aripiprazol eklenmesi faydalı olabilir.…”
Section: Discussionunclassified
“…3,4 Hem dürtü kontrol bozukluklarında hem de OKB'de aripiprazolün faydalı olabileceği bazı çalışmalarda gösterilmiştir. 6,7 Bu yazıda literatürde daha önce bildirilmemiş olan essitalopram tedavisine aripiprazol eklenmesiyle başarılı bir şekilde tedavi edilen onikofaji vakasını sunmayı amaçladık. …”
unclassified
“…Indeed, neurons in the midbrain raphe nuclei project to the ventromedial the treatment of resistant OCD [5,8,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46]. The designs of these studies are heteregenous as regard the duration of the antipsychotic treatment (8 to 12 weeks), the severity of the patients included (Y-BOCS scores), the response criteria (decrease of 25% or 35% of the Y-BOCS) and the presence of comorbidities (including tics and schizotypal personality disorder, not systematically evaluated).…”
Section: Dopaminergic Modelmentioning
confidence: 99%
“…Besides, mood stabilizers, gamma-amino-butyric acid (GABA) analogues and GABA reuptake inhibitors, benzodiazepines and glutamatergic agents are other treatment options (9). Many studies and case reports revealed efficacy of augmentation with antipsychotics, such as aripiprazole, an antipsychotic showing partial agonism at serotonin 5-hydroxytryptamine (5-HT)-1A receptors, and antagonism at 5-HT2A receptors (13), in patients who had inadequate OCD treatment response (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%